Molecular dynamics simulations of the enhanced recovery of confined methane with carbon dioxide. Issue 47 (16th November 2015) - Yuan, Quanzi; Zhu, Xueyan; Lin, Kui; Zhao, Ya-Pu
Abstract : For the first time, the enhanced recovery of confined methane (CH4 ) with carbon dioxide (CO2 ) is investigated through molecular dynamics simulations. Abstract : For the first time, the enhanced recovery of confined methane (CH4 ) with carbon dioxide (CO2 ) is investigated through molecular dynamics simulations. The adsorption energy and configuration of CH4 and CO2 on the carbon surface were compared, which shows that CO2 is a good candidate in displacing confined CH4 . The energy barrier required for displacing CH4 by CO2 injection was found to depend on the displacement angle. When CO2 approached vertically to the carbon surface, the displacement of CH4 occurred most easily. The curvature and size effects of the carbon nanopores on CH4 recovery were revealed and indicated that there exists an optimum pore size making the displacement occur most efficiently. The underlying mechanisms of these phenomena were uncovered. Our findings and related analyses may help to understand CO2 enhanced gas recovery from the atomic level and assist the future design in engineering.